Overexpression of Cx43: Is It an Effective Approach for the Treatment of Cardiovascular Diseases? - Kerstin Boengler; Beatrice Mantuano; Shira Toledano; Ofer Binah; Rainer Schulz (Biomolecules)
In the heart, Connexin 43 (Cx43) is involved in intercellular communication through gap junctions and exosomes. In addition, Cx43-formed hemichannels at the plasma membrane are important for ion homeostasis and cellular volume regulation. Through its localization within nuclei and mitochondria, Cx43 influences the function of the respective organelles. Several cardiovascular diseases such as heart failure, ischemia/reperfusion injury, hypertrophic cardiomyopathy and arrhythmias are characterized by Cx43 downregulation and a dysregulated Cx43 function. Accordingly, a putative therapeutic approach of these diseases would include the induction of Cx43 expression in the damaged heart, albeit such induction may have both beneficial and detrimental effects. In this review we discuss the consequences of increasing cardiac Cx43 expression, and discuss this manipulation as a strategy for the treatment of cardiovascular diseases.